Islamic Education, Javanese Culture, and the Basic Needs of Migrant Workers' Children: A Critique of Abraham Maslow's Theory - Zainal Arifin; Mubaidi Sulaeman (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2025)
This study aims to critique Abraham Maslow's hierarchy of human needs theory, which continues to serve as a primary reference for assessing human needs from childhood through adulthood. Using a qualitative field research approach, data were collected through interviews and direct observations in the field. The study reveals that Maslow's hierarchy, which positions self-actualization at the peak of needs, requires adaptation to the Javanese cultural context, which influences the Islamic education of migrant workers' children in Seketip Village, Kediri, East Java. The ambiguity surrounding the adequacy of physiological needs, such as food and sleep, can lead to subjective interpretations that may foster egotism, thereby obscuring the objectives of Islamic education. Conversely, Javanese traditions and Islamic teachings provide clear moral guidelines for shaping wise individuals. The study concludes that Islamic education and Javanese culture can serve as supplementary parameters to Maslow's theory, addressing the shortcomings in measuring the satisfaction of unquantifiable needs. With morality as a concrete benchmark, this education can shape children’s character, enabling them to meet basic needs while also providing a strong foundation for life. This need is termed as Fundamental Preconditions, encompassing spiritual and visionary needs, and must be fulfilled from conception through to after birth. Keywords: Maslow's Thought, Children's Basic Needs, Migrant Workers' Children Education, Islamic Education and Javanese